PENGARUH RETURN ON ASSET (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di BEI Tahun 2014 – 2021) - Aditya Citra Purbowo; Hadijah Febriana (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether there is a significant influence between Return On Asset (ROA) and Debt to Equity Ratio (DER) on Company Value Empirical Study of Food and Beverage Sub-Sector Companies Listed on the IDX in 2014-2021, both partially and simultaneously. The method used in this study is a quantitative descriptive research method, using secondary data from financial statements and annual reports of the food and beverage sub-sector for the 2014-2021 period. The population of this study was 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2021 period and the sample of this study was 5 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2021 period, using the purposive judgment sampling method. The data analysis technique used was multiple linear regression with Eviews 12 software. Based on the results of the study, ROA partially had no significant effect on the Company Value variable. This is evidenced by the results of the calculated t value which is smaller than the t table (-1.169915 <1.66298) and the significance is greater than 5% (0.050). DER partially has a positive and significant effect on the Firm Value variable. This can be evidenced by the results of the calculated t value which is greater than the t table (25.27707>1.66298) and the significance is less than 5% (0.050). ROA and DER together have an effect on the Firm Value variable. This can be evidenced by the results of the F statistic value of 0.000000 <F table 3.10 with a significant value less than 0.05. The R Square value is 94.11% and the remaining 5.89% by other variables not examined in this study.